Cultivating the Values of Religious Moderation in Islamic Education Learning - Sunardi, Sunardi; Jamiludin, Jamiludin (Al-Bustan: Jurnal Pendidikan Islam, 2025)
Religious moderation is increasingly pertinent in Indonesia's diverse society. Secondary education plays a strategic role in instilling these values, aiming to cultivate a generation that is tolerant and respectful of differences. This study, conducted at SMA Negeri Bareng Jombang, employs a qualitative case study approach to explore how religious moderation is taught. Data was gathered through observations, in-depth interviews with teachers and students, and analysis of curriculum and teaching materials. The findings reveal that religious moderation values have been integrated into various subjects, particularly Islamic Religious Education. Students demonstrate a strong understanding of the importance of moderation, reflected in their tolerance toward religious and cultural diversity. However, challenges such as limited time and resources hinder broader implementation.